Mechanics of Composite and Multi-functional Materials, Volume 7 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Ralph, Carter; Silberstein, Meredith; Thakre, Piyush R.; Singh, Raman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Experimental Mechanics of Composite, Hybrid, and Multifunctional Materials, Volume 7  of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the seventh volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on a wide range ofareas, including: Multifunctional Materials Hybrid Materials Novel Composites Nano- and Particle-Reinforced Composites Additive Manufacturing of Composites Digital Imaging of Composites Damage Detection Non-Destructive Evaluation Fatigue and Fracture of Composites Manufacturing and Joining of Composites Advanced Composites Applications.
From the Contents: Mechanics of Multifunctional Wings With Solar Cells for Robotic Birds -- Optimization of Magnetic and Electrical Properties of New Aluminium Matrix Composite Reinforced With Magnetic Nano Iron Oxide (Fe3O4) -- Manufacturing and Characterization of Non-Isotropic Membranes for Micro Air Vehicles -- Compliant Artificial Skins to Enable Robotic Sensing and Training by Touch -- Electrical Impedance Spectroscopy for Structural Health Monitoring -- Soliton-based Sensor/Actuator for Delamination and Weak Bond Detection in Laminated Composites.
Keywords: Mechanics, Applied; Materials -- Analysis; Materials; Engineering Mechanics; Characterization and Analytical Technique; Materials Engineering